Production potential, economic analysis and energy auditing for maize (Zea mays)-vegetable based cropping systems in Eastern Himalayan Region, Arunachal Pradesh - CHOUDHARY, V K; KUMAR, P SURESH; SARKAR, SUSHEEL KUMAR; Y, J S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 2008-11 to study the production, economics and energy auditing of maize (Zea mays L.)–vegetable cropping system. Maize was grown on terraces during rainy season and vegetables (tomato, okra, frenchbean, pea, potato, cabbage and cauliflower) were grown as sequential crops. Maize equivalent yield (MEY), production efficiency, return per rupee investment and marginal return to marginal cost ratio were recorded higher on maize–tomato cropping system followed by maize–cauliflower. However, the land use efficiency was recorded higher on maize–potato cropping system. Similarly, maize–tomato system generated employment for 175 days followed by maizepotato (150 days). Maize–potato system required highest energy input followed by maize–tomato. But the total output, net energy and output: input ratio of energy was recorded highest on maize–frenchbean system followed by maize–tomato. Specific energy was measured highest on maize–potato system (3.39 MJ/kg), while maize–cauliflower system recorded the highest energy productivity (1.14 kg/MJ). Similarly, maize–frenchbean system recorded highest energy-use efficiency (1257%) and the least energy-use efficiency was recorded on maize–potato system (223%). Maize-tomato system required highest direct energy and maize–potato system required highest indirect energy. However, maize–potato system largely depended on renewable and commercial energy, whereas maize-tomato system extensively relied on non-renewable and non-commercial energy.